2017
DOI: 10.1097/sih.0000000000000189
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Medical Simulation in Teaching Medical Students Critical Care Medicine

Abstract: We aimed to assess effectiveness of simulation for teaching medical students critical care medicine and to assess which simulation methods were most useful. We searched AMED, EMBASE, MEDLINE, Education Resources Information Centre, British Education Index, Australian Education Index, and bibliographies and citations, in July 2013. Randomized controlled trials comparing effectiveness of simulation with another educational intervention, or no teaching, for teaching medical students critical care medicine were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(28 citation statements)
references
References 59 publications
2
22
0
4
Order By: Relevance
“…The findings showed that dialogued lecture and clinical simulation enabled the acquisition of theoretical concepts for wound evaluation and treatment. These results are consistent with studies that have shown clinical simulation to be an effective strategy for improving clinical performance but to have little effect on knowledge acquisition when compared with other educational methods (Beal et al, 2017;Hoffmann, O'Donnell, & Kim, 2007;McCoy et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings showed that dialogued lecture and clinical simulation enabled the acquisition of theoretical concepts for wound evaluation and treatment. These results are consistent with studies that have shown clinical simulation to be an effective strategy for improving clinical performance but to have little effect on knowledge acquisition when compared with other educational methods (Beal et al, 2017;Hoffmann, O'Donnell, & Kim, 2007;McCoy et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…The data obtained in this research in combination with other evidence from the literature confirm that clinical simulation is effective for the development of nursing students' clinical reasoning in wound evaluation and treatment and that clinical simulation in conjunction with other educational methods promotes the acquisition of knowledge by promoting the transition from what the student knows to rational action (Beal et al, 2017;McCoy et al, 2011).…”
Section: Discussionsupporting
confidence: 70%
“…Simulation is a widely used model of medical training, allowing incorporation of practical, hands-on skills training outside of the classroom. 3 Shortridge et al 4 discussed the need for rural telemedicine in Oklahoma, which echoes the need throughout the US. 5 We have implemented a telemedicine simulation curriculum in our family medicine core clinical experience (clerkship) as a mechanism to train future providers to practice in rural or remote locations where patients may not be able to reach a health care facility.…”
Section: Introductionmentioning
confidence: 99%
“…This idea is supported by the literature, which demonstrates simulation training is better than other forms of instruction method such as didactic or problem-based learning and should serve as an adjunct to other instruction methods. 2,38,39 This point is particularly important because interns or junior doctors are the first medical responders called to attend acutely deteriorating patient in a ward and their suboptimal management might put patients at risk or delay appropriate treatment. 21,29 The General Medical Council of the United Kingdom also recommends the use of simulation technology in medical school.…”
Section: Gaps In Undergraduate Medical Educationmentioning
confidence: 99%